2018
DOI: 10.3847/1538-4357/aad328
|View full text |Cite
|
Sign up to set email alerts
|

The Photochemistry of Purine in Ice Analogs Relevant to Dense Interstellar Clouds

Abstract: The aromatic nitrogen heterocyclic compound purine is the core structural framework of many important biomolecules, particularly nucleobases. Purine and purine derivatives have been observed in carbonaceous chondrites, and it has been hypothesized that the exogenous delivery of these compounds, along with many other biologically relevant compounds, may have played a role in the emergence of life. Numerous experiments in our laboratory have demonstrated that the nucleobases used by life to encode genetic materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…40 Related photon processing of H 2 O:NH 3 :purine ices results in the formation of adenine, guanine, and other substituted purine derivatives. 41,47 Interestingly, apart from photon irradiation of simple H 2 O:Pym ices leading to thymine formation, all other photon processing results in the production of RNA nucleobases and thus supports the hypothesis of RNA being the first type of genetic material used by early life. 48 The Pym nucleobases inherit certain properties like their geometry and core and valence electronic structure from the parent Pym moiety, 49,50 which renders this N-heterocycle a subject of demanding attention.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…40 Related photon processing of H 2 O:NH 3 :purine ices results in the formation of adenine, guanine, and other substituted purine derivatives. 41,47 Interestingly, apart from photon irradiation of simple H 2 O:Pym ices leading to thymine formation, all other photon processing results in the production of RNA nucleobases and thus supports the hypothesis of RNA being the first type of genetic material used by early life. 48 The Pym nucleobases inherit certain properties like their geometry and core and valence electronic structure from the parent Pym moiety, 49,50 which renders this N-heterocycle a subject of demanding attention.…”
Section: Introductionsupporting
confidence: 58%
“…37,38 It has been proposed that such N-containing macromolecules may be synthesized through complex reactions between abundant N-bearing species such as NH 3 or HCN and carbonaceous precursors in interstellar ice grains under the influence of UV photons and cosmic ray analogs (e.g., protons and electrons). [39][40][41][42][43] Recent laboratory experiments under interstellar-like conditions demonstrate the formation of uracil and cytosine upon UV irradiation of H 2 O:Pym and H 2 O:NH 3 :Pym ices, respectively. 44,45 These experiments triggered theoretical investigations to gain further insight into the involved chemical conversion scheme.…”
Section: Introductionmentioning
confidence: 99%
“…near or above room temperature), there are no reports on the formation of nucleobases from abundant molecules in interstellar ices through the combination of photolysis at astrophysically relevant low temperatures and subsequent thermal processes. In particular, due to the limited number of related studies 14 , the mechanism of formation of nitrogen-containing heterocyclic rings including purine and pyrimidine, which are the basic structures of nucleobases and have been utilised in previous studies for nucleobase production 2124 , from a mixture of abundant molecules in interstellar ices remains controversial. To understand the prebiotic evolution of biologically important chemical species in molecular clouds, the development of a synthetic pathway mimicking that process would be of pivotal importance.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 25 years, laboratory experiments simulating the photo-irradiation or particle bombardment of mixtures of astrophysical ice analogs at low temperatures (10‒80 K) have shown that organic compounds can form under astrophysical, non-biological conditions. In particular, the ultraviolet (UV) irradiation of ice mixtures consisting of H 2 O, CH 3 OH, CO, CO 2 , CH 4 , and/or NH 3 leads to the formation of compounds of astrobiological interest such as amino acids 1416 , nucleobases 17,18 , functionalized polycyclic aromatic hydrocarbons (PAHs) 19,20 , amphiphiles 21 , as well as urea, hydantoin, and small aldehydes 2224 . A variety of organic compounds have also been shown to form at 5 K when ice mixtures containing CH 3 OH were UV irradiated or bombarded with energetic electrons 25,26 .…”
Section: Introductionmentioning
confidence: 99%